A Morphophonological Analysis of the Applicability of Nasalisation Principles in Lungu, Mambwe and Namwanga Languages - Pethias Siame; Felix Banda; Humphrey Kapau; Benjamin Amoakohene (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The paper explores the similarities and variations in the applicability of nasalisation principles in Lungu, Mambwe and Namwanga (LuMaNa) languages. LuMaNa languages are spoken in Northern and Muchinga provinces of Zambia. Lungu is classified as M14, Mambwe as M15 and Namwanga as M22. The study used CV phonology and comparative Bantu morphophonological theories and qualitative methods. Results reveal that nasal homorganic assimilation depends on the consonant which follows the nasal, such as, a voiceless cluster /nk/ when a voiceless velar /k/ follows /n/ and a voiced cluster /ng/ when a voiced velar /g/ follows /n/. Nasal deletion before fricatives from singular to plural forms of nouns are not attested, instead the languages undergo nasal maintenance where /n/→/n/. Nasal deletion before fricatives is only possible during the reverse formation from plural to singular nouns where /m/→/l/ and /n/→/l/. The post-nasal stop voicing happens when converting singular to plural nouns where /l/→/n/. Post-nasal consonant hardening occurs when converting nouns from singular to plural using /l/→/d/, /n/→/m/ and /w/→/b/. Post-nasal stop aspiration only occurs in Namwanga when the voiceless consonant follows a nasal as in; /p/→/ph/. There are more similarities than variations during nasalisation which shows that LuMaNa languages are at dialectal continuum.